Influence of low-temperature plasma and γ radiation on the surface properties of PET track membranes; Inorganic Materials: Applied Research; Vol. 7, iss. 5 - Filippova E. O. Ekaterina Olegovna; Karpov D. A. Dmitriy Andreevich; Gradoboev A. V. Aleksandr Vasilyevich; Sokhoreva V. V. Valentina Viktorovna; Pichugin V. F. Vladimir Fyodorovich (2016, 2016)
Title screen